Pelatihan Sadar Wisata Berbasis Budaya Sapta Pesona Bagi Host dan Guest di Manahayu Resort and Farm Desa Giripurno Bumiaji Kota Batu - Rhiza E Purwanto; lidiawati lidiawati; Mardiana diana (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2023)
Socialization and training on tourism awareness is the first thing that is important to understand to the entire community as stakeholders who have the same goal in realizing a tourist destination. With this conscious socialization of tourism, it will be able to provide changes to the community to then be able to actively participate in building a tourist destination in their area. Efforts to increase tourism awareness for the community, especially tourism business actors at Manahayu Resort and Farm, are very important because the resort is still in the development stage. The resort, which is located in Giripurno Village, has potential in agriculture and is quite good at empowering its people. However, tourism actors still need to get various trainings related to tourism. This community service is one of the steps in improving the quality and capacity of human resources. The method used is the technique of participatory two-way lectures. The community in this activity is stimulated to discuss more interactively. As a result, the community can understand precisely the importance of developing a sapta pesona based tourist destination in order to go to a tourist village that is able to empower local communities.